Behçet‘s Syndrome Apart From the Triple Symptom Complex: Vascular, Neurologic, Gastrointestinal, and Musculoskeletal Manifestations. A Mini Review - Kötter, Ina; Lötscher, Fabian (Frontiers in Medicine, 2021)
Behçet‘s Syndrome (BS) is a variable vessel vasculitis according to the Chapel Hill Consensus Nomenclature (1) and may thus affect any organ, including major and minor arterial and venous vessels to a varying degree and with varying frequency. Although the main features of BS are recurrent oral and genital aphthous ulcers, cutaneous lesions, ocular inflammation and arthritis—major vessel and life—or organ threatening involvement of internal organs and the central and peripheral nervous system occur. In general, BS in Europe appears to form six phenotypes of clinical manifestations (2), which are (1) mucocutaneous only, (2) predominant arthritis/articular involvement, (3) vascular phenotype, (4) ocular manifestations, which are most likely associated with CNS manifestations and HLA-B51, (5) dominant parenchymal CNS manifestations (being associated with the ocular ones), and (6) gastrointestinal involvement. Mucocutaneous manifestations are present in almost all patients/all phenotypes. In the following review, we summarize the current knowledge concerning vascular, neurologic, gastrointestinal and musculoskeletal manifestations of the disease.